Investigation of interaction of nuclear fast red with human serum albumin by experimental and computational approaches - Gholivanda, Mohammad Bagher (2013)
For the first time, interaction of nuclear fast red (NFR) with human serum albumin (HSA) was studied by experimental and computational approaches. Firstly, experimental measurements including fluorescence spectroscopy (F), UVvis spectrophotometry (UVvis), cyclic voltammetry (CV), differential pulse voltammetry (DPV) and linear sweep voltammetry (LSV) were separately used to investigate the interaction of NFR with HSA and interesting thermodynamics information was obtained from these studies. Secondly, new information including electrochemical behavior of NFR–HSA complex species, relative concentrations of the various reacting species and effects of NFR on the sub-structure of HSA was obtained by applying multivariate curve resolution–alternating least squares (MCR–ALS). In this case, a row- and column-wise augmented matrix was built with DPV, LSV, F and UVvis sub-matrices and resolved by MCR–ALS. Surprisingly, by this method two NFR–HSA complex species with different stoichiometries and different electrochemical behaviors were found. Furthermore, by the use of the recorded voltammetric and spectroscopic data the binding constants of complex species were computed by EQUISPEC (a hard-modeling algorithm). Finally, the binding of NFR to HSA was modeled by molecular modeling and molecular dynamics (MD) simulations methods. Excellent agreement was found between experimental and computational results. Both experimental and computational results suggested that the NFR binds mainly to the sub-domain IIA of HSA.